The Influence of Public Service Motivation on Service Quality of Civil Servants in West Sumatra Indonesia - Syamsir, Syamsir (European Journal of Economics and Business Studies, 2016)
Background ¬– Most of PSM studies tend to conclude that PSM cases and theories are cross-culturally viable. Besides, so far, most PSM research focuses more on employees (public and private) in the Western and developed countries; and almost no study of the PSM in developing countries. In addition, most of the PSM theories tended to generalize the assumptions of the PSM among employees and often ignore cultural dimensions in their analysis, including in relation to the effect of PSM on the quality of work. Purpose – The purpose of this study was to find out the influence of Public Service Motivation (PSM) on service quality of civil servants in a wide range of government agencies in the province of West Sumatra. Design/methodology/approach – This study used quantitative methods. Data were collected through proportional stratified random sampling from a sample consisted of 1,270 respondents from some government institutions in West Sumatra province. Data were analyzed with multiple regression analysis. Finding – The finding of this study indicated that the overall public service motivation significantly influenced on the service quality of civil servants in a wide range of government agencies in West Sumatra province. Besides, the results of this study also indicated that the PSM dimension associated with commitment to public interest have a greater influence than the other dimensions of PSM, namely attraction to public policy making, compassion, and self sacrifice. Practical Implications – This study would be offering a consideration and advice to the local government about the need to consider the aspects of public service motivation in improving the service quality of civil servants, especially in West Sumatra Indonesia.
Keywords: Public Service Motivation (PSM), service quality, civil servants